Design Of Public Service Announcement for Appropriate Sexual Education and Supervision for Underage Children - Naifa Khansa Lintang Anjani; Daniar Wikan Setyanto (Judikatif: Jurnal Desain Komunikasi Kreatif, 2025)
The increasing cases of sexual violence and abuse against minors, particularly in Semarang City, reflect a lack of sexual education and weak supervision from their immediate environment. This design project aims to provide a visual solution in the form of educational media that raises awareness among both children and parents about the importance of early self-protection. This study employs a qualitative research method with data collection techniques including observation, literature review, documentation, and interviews. The design approach follows Robin Landa’s creative process, which emphasizes development from research to production. This research is limited to the Semarang area, targeting school-aged children, teenagers, and parents. The final output includes a main media in the form of an illustrated storybook, supported by additional media such as stickers, tote bags, and pouches. The book delivers sexual education through bright illustrations, appealing characters, and simple language. Evaluation results indicate that the design is effective in delivering educational messages and enhancing parental involvement in child supervision. It is expected that this media can serve as an initial step in preventing sexual violence against children.